2021
DOI: 10.1097/ccm.0000000000004935
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Sedation With Dexmedetomidine on Body Temperature in Critically Ill Patients*

Abstract: OBJECTIVES: Previous case series reported an association between dexmedetomidine use and hyperthermia. Temperature data have not been systematically reported in previous randomized controlled trials evaluating dexmedetomidine. A causal link between dexmedetomidine administration and elevated temperature has not been demonstrated. DESIGN: Post hoc analysis. SETTING: Four ICUs in Australia and New Zealand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
2
20
2
Order By: Relevance
“…18 In contrast to our study, this analysis reported a high rate of hyperthermia, with a number needed to harm of 15 for patients with a temperature ≥39°C. 18 One potential explanation for this discrepancy is the use of strict selection criteria in our study, minimizing the possibility of potential confounders on elevations in body temperature. Another finding of the aforementioned study was that patients greater than 120 kg were more likely to develop increases in body temperature ( P = .02), which is consistent with a previous study conducted by the same group that identified obesity as a potential risk factor for DSF.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…18 In contrast to our study, this analysis reported a high rate of hyperthermia, with a number needed to harm of 15 for patients with a temperature ≥39°C. 18 One potential explanation for this discrepancy is the use of strict selection criteria in our study, minimizing the possibility of potential confounders on elevations in body temperature. Another finding of the aforementioned study was that patients greater than 120 kg were more likely to develop increases in body temperature ( P = .02), which is consistent with a previous study conducted by the same group that identified obesity as a potential risk factor for DSF.…”
Section: Discussioncontrasting
confidence: 93%
“…The findings of our study echo the results reported by Grayson and colleagues in a post-hoc analysis of the SPICE III Trial, in which significantly more patients treated with dexmedetomidine versus other sedatives had temperatures greater than or equal to 38.3°C (43.3% vs. 32.7%, P = .004) and 39.0°C (19.4% vs. 12.5%, P = .013). 18 In contrast to our study, this analysis reported a high rate of hyperthermia, with a number needed to harm of 15 for patients with a temperature ≥39°C. 18 One potential explanation for this discrepancy is the use of strict selection criteria in our study, minimizing the possibility of potential confounders on elevations in body temperature.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations